Bioprospecting a native silver-resistant Bacillus safensis strain for green synthesis and subsequent antibacterial and anticancer activities of silver nanoparticles - Ahmed, Temoor (J Adv Res, 2020)
Green nanomaterials have gained much attention due to their potential use as therapeutic agents. The present study investigated the production of silver nanoparticles (AgNPs) from a silver-resistant Bacillus safensis TEN12 strain, which was isolated from metal contaminated soil and taxonomically identified through 16S rRNA gene sequencing. The formation of AgNPs in bacterial culture was confirmed by using UV–vis spectroscopy with an absorption peak at 426.18 nm. Fourier transform infrared (FTIR) spectroscopy confirmed the involvement of capping proteins and alcohols for stabilization of AgNPs. Moreover, X-ray diffraction analysis (XRD), scanning and transmission electron microscopy (SEM and TEM) confirmed the crystalline nature and spherical shape of AgNPs with particle size ranging from 22.77 to 45.98 nm. The energy dispersive X-ray spectroscopy (EDX) revealed that 93.54% silver content is present in the nano-powder. AgNPs showed maximum antibacterial activity (20.35 mm and 19.69 mm inhibition zones) at 20 µg mL(−1) concentration against Staphylococcus aureus and Escherichia coli, respectively and significantly reduced the pathogen density in broth culture. Furthermore, AgNPs demonstrated significant anticancer effects in the human liver cancer cell line (HepG2) in MTT assay, whereas, no cytotoxic effects were demonstrated by AgNPs on normal cell line (HEK293). The present study suggests that the biogenic AgNPs may substitute chemically synthesized drugs with wider applications as antibacterial and anticancer agents.